2010
DOI: 10.1007/s10439-010-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Endothelial Cells to Simvastatin When Conditioned with Steady, Non-Reversing Pulsatile or Oscillating Shear Stress

Abstract: Few studies have investigated whether fluid mechanics can impair or enhance endothelial cell response to pharmacological agents such as statin drugs. We evaluated and compared Kruppel-like factor 2 (KLF2), endothelial nitric oxide synthase (eNOS), and thrombomodulin (TM) expression in human abdominal aortic endothelial cells (HAAEC) treated with increasing simvastatin concentrations (0.1, 1 or 10 μM) under static culture and shear stress (steady, non-reversing pulsatile, and oscillating). Simvastatin, steady f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…With respect to KLF2, researchers have also reported that atheroprotective laminar shear stress, through suppression of miR-92a, can upregulate endothelial TM via KLF2-dependent transactivation of the TM promoter (35, 187). Interestingly, the pleiotropic upregulation of endothelial TM by statins was only observed under atheroprotective shearing conditions (consistent with miR-92a suppression and KLF2 induction), and not under conditions of atherogenic oscillatory shear (128). These collective observations suggest that statinmediated pleiotropic effects on TM are restricted to shearprotected regions of the endothelium and putatively involve suppression of miR-92a.…”
Section: Therapeutic Considerationsmentioning
confidence: 65%
“…With respect to KLF2, researchers have also reported that atheroprotective laminar shear stress, through suppression of miR-92a, can upregulate endothelial TM via KLF2-dependent transactivation of the TM promoter (35, 187). Interestingly, the pleiotropic upregulation of endothelial TM by statins was only observed under atheroprotective shearing conditions (consistent with miR-92a suppression and KLF2 induction), and not under conditions of atherogenic oscillatory shear (128). These collective observations suggest that statinmediated pleiotropic effects on TM are restricted to shearprotected regions of the endothelium and putatively involve suppression of miR-92a.…”
Section: Therapeutic Considerationsmentioning
confidence: 65%
“…Previous studies by our group have demonstrated the effectiveness in using these models to expose ECs to LSS [16,2527,3236]. Specifically, HAAECs were exposed to 10 dynes/cm 2 of LSS for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed protocols for the 3D cell culture models and flow apparatus have been described previously [16,2527]. Briefly, straight tube models (hemodynamic parameters within the model are summarized in Table 1) were made by mounting polished stainless steel rods into pre-designed molds.…”
Section: Methodsmentioning
confidence: 99%
“…Atorvastatin induced the vasculoprotective heme oxygenase-1 expression through the Akt pathway, mainly at sites of laminar stress (Ali et al, 2009a). Endothelial response to statins could be therefore affected by wall shear stress, because it has been recently observed that the protective action of simvastatin depends on the hemodynamic forces, being compromised by low shear stress with reversing flow (Rossi et al, 2011).…”
Section: B Statins and Endothelial Functionmentioning
confidence: 99%